2008
DOI: 10.1111/j.1465-7295.2007.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Noncognitive Skills in Explaining Cognitive Test Scores

Abstract: This paper examines whether noncognitive skills -measured both by personality traits and economic preference parameters -influence cognitive tests performance. The basic idea is that noncognitive skills might affect the effort people put into a test to obtain good results. We experimentally varied the rewards for questions in a cognitive test to measure to what extent people are sensitive to financial incentives. To distinguish increased mental effort from extra time investments we also varied the questions' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
205
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(223 citation statements)
references
References 9 publications
11
205
0
7
Order By: Relevance
“…Caliendo et al (2015) and McGee (2015) find that unemployed individuals with an internal locus of control invest more into job search than externally controlled individuals. Similarly, Cobb-Clark et al (2014) find that internally controlled individuals invest more into health capital and Borghans et al (2008) document that they perform better on cognitive tests. Cobb-Clark and Schurer (2013) show that they also accumulate more precautionary savings, and Salamanca et al (2016) find that internal locus of control is positively related to investments in risky assets.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Caliendo et al (2015) and McGee (2015) find that unemployed individuals with an internal locus of control invest more into job search than externally controlled individuals. Similarly, Cobb-Clark et al (2014) find that internally controlled individuals invest more into health capital and Borghans et al (2008) document that they perform better on cognitive tests. Cobb-Clark and Schurer (2013) show that they also accumulate more precautionary savings, and Salamanca et al (2016) find that internal locus of control is positively related to investments in risky assets.…”
Section: Introductionmentioning
confidence: 97%
“…If locus of control can have ambiguous effects on the quality of economic decisions, this has implications for the economic literature that analyzes the impact of non-cognitive skills on economic behaviors and outcomes (see, e.g., Borghans et al 2008, Chiteji 2010, or Grönqvist et al 2016. Non-cognitive skills are often viewed as characteristics that enhance the productive capacity of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Becker et al (2012) empirically explore three datasets to link personality traits to economic preference parameters and find complementarity between the two. Borghans et al (2008b) find that performance motivation, fear of failure, internal locus of control, curiosity, low discount rates, and risk aversion are positively associated with more correct answers on a cognition test. Our results are also consistent with experimental evidence from Sutter et al (2012), who find that students with higher levels of impulse control fare better in school and are more likely to obtain good labour-market outcomes.…”
mentioning
confidence: 93%
“…Indeed, non-cognitive skills have been found to be important for performance on IQ tests due to the low stakes nature of the latter. As shown by Borghans et al (2008); Duckworth et al (2011);Gneezy and Rustichini (2000) and Segal (2012), scores of low performers on IQ tests can be improved by offering a reward. As mentioned above, some of this literature have explicitly proposed a decomposition of test scores into a cognitive and a non-cognitive component, see Borghans and Schils (2012).…”
Section: Measures Based On the Background Questionnairementioning
confidence: 99%
“…Hedengren and Stratmann (2012) found that survey non-response is both correlated with cognitive and non-cognitive skills and, consequently, it may be interpreted as a measure of the two types of skills. Indeed, as recognized by Borghans et al (2008), separating cognitive ability from non-cognitive skills is not only empirically, but also conceptually complicated. However, in the line of Hitt et al (2016), we consider survey nonresponse to be a measure of non-cognitive skills rather than cognitive ability (despite being correlated with the two).…”
Section: Measures Based On the Background Questionnairementioning
confidence: 99%